Harnessing a high cargo-capacity transposon for genetic applications in vertebrates. - Darius Balciunas; Kirk J Wangensteen; Andrew Wilber; Jason Bell; Aron Geurts; Sridhar Sivasubbu; Xin Wang; Perry B Hackett; David A Largaespada; R Scott McIvor; Stephen C Ekker (PLoS Genetics)
Viruses and transposons are efficient tools for permanently delivering foreign DNA into vertebrate genomes but exhibit diminished activity when cargo exceeds 8 kilobases (kb). This size restriction limits their molecular genetic and biotechnological utility, such as numerous therapeutically relevant genes that exceed 8 kb in size. Furthermore, a greater payload capacity vector would accommodate more sophisticated cis cargo designs to modulate the expression and mutagenic risk of these molecular therapeutics. We show that the Tol2 transposon can efficiently integrate DNA sequences larger than 10 kb into human cells. We characterize minimal sequences necessary for transposition (miniTol2) in vivo in zebrafish and in vitro in human cells. Both the 8.5-kb Tol2 transposon and 5.8-kb miniTol2 engineered elements readily function to revert the deficiency of fumarylacetoacetate hydrolase in an animal model of hereditary tyrosinemia type 1. Together, Tol2 provides a novel nonviral vector for the delivery of large genetic payloads for gene therapy and other transgenic applications.